Lower Bound for the Class Number of ℚn2+4 - Hasan Sankari; Ahmad Issa (International Journal of Mathematics and Mathematical Sciences)
In this paper, we give an explicit lower bound for the class number of real quadratic field ℚd, where d=n2+4 is a square-free integer, using  ωn which is the number of odd prime divisors of n.